Exploring the Impact of Metacognitive Strategy on University Student Reading Performance - Yudhodibroto, Adityo; Lolita, Yuri (IJET (Indonesian Journal of English Teaching), 2024)
The purpose of this study was to find a relationship between EFL students' metacognitive awareness of reading strategies and reading comprehension. The research design uses quantitative, the sample required is 63 EFL students as participants, using reading comprehension scores and questionnaires to improve Metacognitive Awareness Reading Strategies in students. Metacognitive Awareness of Reading Strategy Inventory (MARSI-R) and Reading Test in the Essential Reading course to determine the level of students' metacognitive awareness. The results of this study indicate that 51 students or 81% can be categorized as high group level, and 10 students or 18% can be categorized as medium group level and for low category get 2 students or 3%.This research shows that the most used strategy by EFL learners is found using PRS (Problem solving strategy) found mean is 3.21; GRS (Global reading strategy) found mean is 3.41; and, SRS (Supports reading strategies) found mean is 3.02. For correlation, the Spearman Rho coefficient results show that there is no relationship between EFL students' metacognitive awareness of reading strategies and reading comprehension.